The Role of the School’s Committee in Implementing P5 in the Era of Independent Learning - Nurhayati, Nurhayati; Martiarini, Elyza; Nurjanah, Nurjanah (PPSDP International Journal of Education, 2024)
The purpose of this study was to determine the role of the school committee and its contribution in improving the quality of education in the era of independent learning. This study was conducted at SMP Negeri West Jakarta Region 1. Interviews, observations, documentation, and literature reviews were the data collection tools used. This study is qualitative research with a descriptive analysis method. The data collection process was carried out through in-depth interviews and questioner. The technique of data analysis was classifying data based on the category, counting the frequency and percentage. This study found that the school committee, as part of the school element, is responsible for the smooth implementation of school programs in the current era of independent learning, the implementation of the Pancasila Student Profile Strengthening Project (P5), building relationships with the school community, improving facilities and infrastructure, and encouraging improvements in the quality of school resources. Here, the result of the percentage of each the categories they are: an advisory agency (consideration) as much as 25%, a support agency (supporter) as much as 25%. a controlling agency (controller) as much as 23% and a mediator as much as 27%.